Visitor value perception of a heritage tourism site development: a case study - Taylor, Ruth; Shanka, Tekle (Cognizant Communication Corporation, 2008)
Successful tourism attraction site development includes the ability to design and deliver unique, authentic products, services, and experiences for visitors. Value perception is an important strategic imperative for management and a decision imperative for visitors in that it represents both short-term and long-term benefits and sacrifices to both attraction and visitor. This research study discusses visitor value perception, and investigates the expectations of visitors to a proposed development associated with a prime tourism attraction site development. A total of 960 useable questionnaires were analyzed to provide the findings of this study. It was identified that while a range of product offerings were available at the site, the core identity valued by visitors was that of heritage. The research project found that overall the proposed development of the tunnels project was thought to enhance this element of the site, while allowing additional services to be developed in the form of an adventure experience. Results are discussed and implications for the project development are identified.